Co-gasification of rice production wastes - André, Rui Neto (2015)
Rice production is one of the major food sources in the world and unavoidably generates large amounts of wastes, mainly husk and straw that must be dealt in an environmentally sound and sustainable way. Traditional solutions, like burning in open fields or soil incorporation, may contribute for local pollution. Even the use of these wastes as animal food is not an appropriate solution. Plastics are also an additional waste arising from the life cycle of rice production, manufacturing and distribution. The co-gasification of these wastes was easily accomplished in a fluidized bed installation using steam mixed with air or oxygen as gasifying and fluidisation agents. By changing the gasifying agent composition it is possible to select the best conditions to co-gasify rice husks and PE wastes blends. For rice husks gasification, highest H2/hydrocarbons molar ratios were obtained using a mixture of air and steam and an equivalent ratio of 0.2. These conditions correspond to low tar emissions and very good gas yields and gas higher heating values (HHV). Co-gasification of rice husk mixed with PE enables to increase gas HHV, but also generates more tar. Nevertheless using up to 20 % of PE can be considered a promising solution to deal with this kind of wastes. Pollutants like H2S and NH3 were formed in the gasification process in acceptable amounts. Co-gasification with PE enables to decrease these pollutants. Depending on the gas end-use, the installation of a hot gas conditioning system could be needed to further decrease the contents of tar, H2S and NH3, while also promoting the conversion of hydrocarbons into H2 and CO.